A silver self‐assembled monolayer‐decorated polydimethylsiloxane flexible substrate for in situ SERS detection of low‐abundance molecules. (28th June 2018) - Zhao, Hang; Hasi, Wuliji; Bao, Lin; Liu, Yuping; Han, Siqingaowa; Lin, Dianyang
Abstract: The preparation of highly sensitive and low cost substrate remains challenging in surface‐enhanced Raman spectroscopy (SERS). Here, a simple silver nanoparticle‐modified thin polydimethylsiloxane (PDMS) sheet was prepared as a SERS substrate via silicon‐assisted interfacial self‐assembly transfer and Langmuir–Schaefer deposition technique. The influence of the surface coverage on PDMS was investigated and optimized to achieve the maximal signal enhancement. Through the test of rhodamine 6G and 4‐mercaptobenzoic acid probe, the substrate showed good uniformity of nanoparticles, high‐enhanced factor, homogeneity of batch, time stability, and other properties. We, then, measured thiram and tricyclazole pesticides on the surface of apples, and the results demonstrate that SERS substrates can measure pesticide residues in situ. Abstract : A simple silver nanoparticle‐modified thin PDMS sheet was prepared as a SERS substrate via silicon‐assisted interfacial self‐assembly transfer and Langmuir–Schaefer deposition technique. The influence of the surface coverage on PDMS was investigated and optimized to achieve the maximal signal enhancement. The substrate showed good uniformity of nanoparticles, high‐enhanced factor, and other properties. We, then, measured thiram and tricyclazole pesticides on the surface of apples, and the results demonstrate that SERS substrates can measure pesticide residues in situ.